KARAKTERISASI ADSORBEN ZEOLIT YANG DIAKTIVASI - Novi Indriyana Lestari, ; Siti Tjahjani, (Matematika dan Sains, 2009)
Reseach was carried out to find the characteristic of zeolite adsorben before and after activated by HCl followed by calcination. Decreasing of metal ion concentration was analyzed using AAS, functional group characterization by IR spectroscopy. Results of research showed that the natural zeolite which activated by HCl 0.2 M indicated the decreasing of Na+ concentration from 3.6875 mg/L to 2.4781 mg/L and for Ca2+ from 1.9214 mg/L to 1.8571 mg/L. The IR spectrum of natural zeolite showed the presence of O-T-O (T = Si atau Al) (1021,2 cm-1 ) and OH (3408.6 cm-1). While the IR spectrum of zeolite H indicated the existence of O-T-O (T = Si atau Al) (1039,4 cm-1), OH of water (3402.3 cm 1) and Si-OH-Al (3543 cm-1 ). The acid-calcinated zeolite showed absorption band at 1035,2 cm-1 (O-T-O, T = Si or Al) and 3399,7 cm-1 (OH of water). After interacted with indigo carmine, the acid-calcinated zeolite showed absorption at 1036.2 cm-1 (O-T-O, T = Si or Al); 3392.2 cm-1 (OH of water), and 1151.7 cm-1 (S=O of sulfate).+ concentration from 3.6875 mg/L to 2.4781 mg/L and for Ca2+ from 1.9214 mg/L to 1.8571 mg/L. The IR spectrum of natural zeolite showed the presence of O-T-O (T = Si atau Al) (1021,2 cm-1 ) and OH (3408.6 cm-1). While the IR spectrum of zeolite H indicated the existence of O-T-O (T = Si atau Al) (1039,4 cm-1), OH of water (3402.3 cm 1) and Si-OH-Al (3543 cm-1 ). The acid-calcinated zeolite showed absorption band at 1035,2 cm-1 (O-T-O, T = Si or Al) and 3399,7 cm-1 (OH of water). After interacted with indigo carmine, the acid-calcinated zeolite showed absorption at 1036.2 cm-1 (O-T-O, T = Si or Al); 3392.2 cm-1 (OH of water), and 1151.7 cm-1 (S=O of sulfate).